Drowning in fresh or salt water: respective influence on respiratory function in a matched cohort study. (October 2019) - Michelet, Pierre; Dusart, Marion; Boiron, Laurence; Marmin, Julien; Mokni, Tarak; Loundou, Anderson; Coulange, Mathieu; Markarian, Thibaut
Abstract : Introduction: For the most severe drowned patients, hypoxemia represents one of the major symptoms. As the influence of the type of water (fresh or salt water) on respiratory function is still unclear, the primary endpoint of this multicenter study was to compare hypoxemia according to the type of water. Methods: Medical records of adult patients who experienced a drowning event and were consequently admitted to 10 ICU for acute respiratory failure were analyzed retrospectively using data collected over three consecutive summer periods. From an initial cohort of acute respiratory failure drowned patients, patients were matched by age, sex, Glasgow Coma Scale, and occurrence of cardiac arrest (yes or no). Results: Among an initial cohort of 242 patients, 38 pairs were matched correctly. At the initial assessment, carried out upon ICU admission, hypoxemia was found to be deeper in the fresh water group (PaO2 /FiO2 : 141 ± 76 vs. 220 ± 122, P < 0.05). However, there was no significant difference in tissue oxygenation (assessed by blood lactate level) between groups. In terms of biology results, sodium levels were higher in the salt water group in the initial assessment (144 ± 6.8 vs. 140 ±5.2 mmol/l, P = 0.004), but no difference was observed later. No difference was recorded in the outcome or length of stay in ICU between groups. Conclusion: Drowning in fresh water was associated with deeper hypoxemia in the initial assessment. Despite this initial difference, latter respiratory and biological parameters or outcome were similar in both groups.